Carmen Pereira's Os meus três amores: The voice of militant motherhood in Guinea-Bissau. Issue 3 (January 2019) - Rothwell, Phillip
Abstract : In this article, I discuss Os meus três amores by Carmen Pereira. The text subtly reveals her role in overcoming Amílcar Cabral's initial skepticism about the role of women in Guinea-Bissau's revolution. Literary in style, Os meus três amores foregrounds repeated instances of the tension between militancy and motherhood. Its genre-crossing nature – traversing the boundaries between a diary, a memoir, and testimonial with contributions from multiple narrative voices – highlights the complex web of referentiality and authority inherent to autobiographical writing.